Deconstructing the Emotion Regulatory Properties of Mindfulness: An Electrophysiological Investigation - Lin, Yanli; Fisher, Megan E.; Roberts, Sean M. M.; Moser, Jason S. (Frontiers in Human Neuroscience, 2016)
The present study sought to uncover the emotion regulatory properties of mindfulness by examining its effects—differentiated as a meditative practice, state of mind, and dispositional trait—on the late positive potential (LPP), an event-related potential indexing emotional processing. Results revealed that mindfulness as a meditative practice produced a reduction in the difference between the LPP response to negative high arousing and neutral stimuli across time. In contrast, a state mindfulness induction (i.e., instructions to attend to the stimuli mindfully) failed to modulate the LPP. Dispositional mindfulness, however, was related to modulation of the LPP as a function of meditation practice. Dispositional mindfulness was associated with a reduction of the LPP response to negative high arousal stimuli and the difference between negative high arousal and neutral stimuli in participants who listened to a control audio recording but not for those who engaged in the guided meditation practice. Together, these findings provide experimental evidence demonstrating that brief mindfulness meditation, but not deliberate engagement in state mindfulness, produces demonstrable changes in emotional processing indicative of reduced emotional reactivity. Importantly, these effects are akin to those observed in individuals with naturally high dispositional mindfulness, suggesting that the benefits of mindfulness can be cultivated through practice.